A Novel Technique for the Metrology Calibration of a Fourier Transform Spectrometer - Locke D. Spencer; David A. Naylor (Fourier Transform Spectroscopy/ Hyperspectral Imaging and Sounding of the Environment, 2007)
n/a
Keywords: and metrology; Instrumentation; Interferometry; measurement; Spectrometers and spectroscopic instrumentation